2022
DOI: 10.36457/gizindo.v45i2.731
|View full text |Cite
|
Sign up to set email alerts
|

Studi Komparasi Kriteria Global Leadership Initiative on Malnutrition (Glim) Dengan Subjective Global Assesment (Sga) Dalam Mendiagnosis Malnutrisi Pada Pasien Rawat Inap Di Bangsal Penyakit Dalam Rsupn Dr. Cipto Mangunkusumo

Abstract: Malnutrition in hospitalized patients is a global problem with an increasing prevalence. To date, there is no universally accepted consensus for diagnosing malnutrition. Comparative studies between malnutrition criteria according to GLIM and the gold standard, namely Subjective Global Assessment (SGA) have not been widely carried out in Indonesia. This study aims to compare the validity of the GLIM criteria against the SGA. The study design was cross-sectional with the subject of hospitalized internal medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Moreover, the wide prevalence range might be due to different research methodologies and mixed populations. A greater malnutrition proportion at admission in present study has been confirmed by previous findings (GLIM 75% vs. SGA 70.4 %) [34], and supported by Syam et al with malnutrition rate according to SGA have reached 65,5% among non-surgical inpatients [33]. This could be explained by the use of the GLIM which has 2 measurable criteria as the latest validated diagnosis tools which proved has better performance than previous methods in validity, and accuracy in predicting negative clinical outcomes [28,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the wide prevalence range might be due to different research methodologies and mixed populations. A greater malnutrition proportion at admission in present study has been confirmed by previous findings (GLIM 75% vs. SGA 70.4 %) [34], and supported by Syam et al with malnutrition rate according to SGA have reached 65,5% among non-surgical inpatients [33]. This could be explained by the use of the GLIM which has 2 measurable criteria as the latest validated diagnosis tools which proved has better performance than previous methods in validity, and accuracy in predicting negative clinical outcomes [28,[30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically in Indonesia, undernourishment was observed in 26.7-65.5% of adult internal medicine inpatients. (6,24,33) This number has recently tended to be higher when assessed using the GLIM criteria (75.0%) than the SGA (70.4%) [34]. However, the risk factors for malnutrition based on GLIM criteria have not been examined, particularly among inpatients in Indonesia, which has a large population with the highest mortality caused by comorbidity, namely stroke, ischaemic heart disease, diabetes mellitus, lung disease and liver disease [35].…”
mentioning
confidence: 99%